2019
DOI: 10.1186/s12904-019-0483-9
|View full text |Cite
|
Sign up to set email alerts
|

The exploration of the knowledge, attitudes and practice behaviors of advanced care planning and its related predictors among Taiwanese nurses

Abstract: BackgroundDespite the documented and well known patient benefits of ACP, the completion of ACP, only a minority of patients, during the advanced or EOL stage of their illnesses, receive such care. The misconceptions about ACP for healthcare providers, such as nurses, might become potential barriers to the effective implication of ACP. Also, from the transcultural perspective, it is evident essential to explore Taiwanese nurses’ attitudes, knowledge, and actions of ACP. The purposes of this study were to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 31 publications
6
40
2
Order By: Relevance
“…Our results showed that nurses with better ACP attitudes also had better ACP practice with terminally ill patients. Many previous studies have shown similar results [8,10,25]. Attitudes refer to the participant's feelings about the problem, while practice is the way of expressing an attitude.…”
Section: Factors Affecting the Kap-acp Of Terminally Ill Patients Among Nursesmentioning
confidence: 53%
See 2 more Smart Citations
“…Our results showed that nurses with better ACP attitudes also had better ACP practice with terminally ill patients. Many previous studies have shown similar results [8,10,25]. Attitudes refer to the participant's feelings about the problem, while practice is the way of expressing an attitude.…”
Section: Factors Affecting the Kap-acp Of Terminally Ill Patients Among Nursesmentioning
confidence: 53%
“…This study found that nurses with ACP knowledge of terminally ill patients had better attitudes toward the ACP of terminally ill patients. A prior study conducted in Taiwan showed that the better the knowledge of ACP among nurses, the more positive attitude toward ACP [8]. Nurses with ACP knowledge would have greater confidence to enter an ACP discussion with a positive attitude.…”
Section: Factors Affecting the Kap-acp Of Terminally Ill Patients Among Nursesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers from several countries have found that the negative beliefs by nurses impact the ACP process. 24,25 Much current and past literature reiterates that ACP is a complex ongoing process that includes multiple actors and components and can vary greatly by setting and state of health or disease of residents. Providers are one of the critical actors in the ACP process and as such their willingness and education represent essential elements or preconditions for effective ACP.…”
Section: Discussionmentioning
confidence: 99%
“…Advance care planning (ACP) refers to a process of communication and discussion on the patient's expected end-of-life care among the patient, family members, proxy decision-maker, and medical staff [13,14]. In addition to considering the patient's autonomy and values [15], ACP undergoes a continuous communication, preparation, and reflective discussion process, which reduces the emotional stress in caregivers when caring the terminal patients [16].…”
Section: Introductionmentioning
confidence: 99%